Designing An English Supplementary Material Based On Inquiry-Based Learning Focusing On Islamic Values At SMA PPMI Assalam Sukoharjo - Aini, Nurul; , Prof. Dr. Endang Fauziati, M. Hum; , Mauly Halwat Hikmat, Ph.D (2016)
This research is mainly intended to develop materials of English textbook for second grade of Senior High School students based on Inquiry based learning. It develops an "English for Muslim Student" that incorporate Islamic values into textbook. The objectives are to investigate the quality of textbook entitled "Contextual English", to explain how to propose prototype of English supplementary material, and to explain the prototype quality of English supplementary material for SMA PPMI Assalam Sukoharjo. This research is Research and Development (R&D). The objects are "Contextual English" textbook and students of second grade at SMA PPMI Assalam. In collecting the data, the writer uses observation, interview, and documentation. In analyzing the data, the writer does some steps which involve presenting, classifying, describing the data, making conclusion and drawing implication. This research proposes some steps in designing an English material which consist of three stages such as exploring, developing and validating stages. The findings show that the material in chapter 8-10 has been developed by the writer based on five stages in Inquiry based learning (observing, questioning, exploring, associating and communicating). Therefore, the final draft of supplementary material can be used for teaching and learning English in second semester of second grade in SMA PPMI Assalam Sukoharjo.